Production of artificial fingermarks. Part I – Synthetic secretions formulation. (February 2022) - Steiner, Romain; Roux, Claude; Moret, Sebastien
Abstract: Fingermark variability is a critical parameter. To mitigate the effects of this variability, synthetic secretions in the form of simple mixtures of target compounds found in eccrine sweat have been described in the literature, but they are usually reactive towards only a minimal range of detection techniques. If this approach is acceptable for the production of single-technique test strips, such artificial secretions cannot be considered as reliable fingermark simulants because they do not reproduce the complex matrix that makes up real secretions. Research has shown that sebaceous and eccrine compounds are probably present simultaneously in fingermark residue in the form of an emulsion. This paper is the first part of a research project that aims at producing realistic artificial fingermarks containing an extensive range of eccrine and sebaceous compounds. This first study aimed to reproduce and compare two synthetic fingermark residues formulations and assess their potential to be used as fingermark simulants. Spot tests of the artificial secretions were deposited on paper substrates, and their reactivity with four common detection techniques was tested: 1, 2-indanedione-zinc, ninhydrin, oil red O, and physical developer. Both formulations showed very good results when processed with the two amino acid reagents, as well as oil red O, and no obvious differences were observed between the two versions. The results obtained with the physical developer were inconsistent and demonstrated that the fundamental working principle of physical developer needs to be further understood. The results were extremely promising as they showed the potential of such reproducible artificial secretions to be used to assess an extensive range of detection techniques, which would be highly beneficial to guarantee better research and quality control in fingermark detection. The use of spot tests to deposit the simulant was shown to be unreliable and a more controllable and reproducible deposition method using an inkjet printer will be presented in the second part of this research. Highlights: Reproduction and comparison of published artificial secretions. Spot tests of the artificial secretions treated with common detection techniques. Amino acid reagents and ORO gave successful results with both formulations. No obvious difference in reactivity between the two versions. Artificial emulsions have a high potential as fingermark simulants.